2008
DOI: 10.1098/rsif.2008.0068.focus
|View full text |Cite
|
Sign up to set email alerts
|

The enzyme aromatic amine dehydrogenase induces a substrate conformation crucial for promoting vibration that significantly reduces the effective potential energy barrier to proton transfer

Abstract: The role of promoting vibrations in enzymic reactions involving hydrogen tunnelling is contentious. While models incorporating such promoting vibrations have successfully reproduced and explained experimental observations, it has also been argued that such vibrations are not part of the catalytic effect. In this study, we have employed combined quantum mechanical/molecular mechanical methods with molecular dynamics and potential energy surface calculations to investigate how enzyme and substrate motion affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
(60 reference statements)
1
31
0
Order By: Relevance
“…Two opposing and limiting theories of enzyme catalysis revolve around the nature of mechanical and electrostatic fluctuations in the enzyme active site. In one of the theories, fast (approximately picosecond) vibrations (protein breathing modes) and a network of coupled motions within the enzyme-substrate complex have been hypothesized to be linked to transition state formation and reduction of the barrier for chemical change (10,13,15,21). It has also been suggested that dynamic excursions of active site architecture on the picosecond timescale create variable electronic interactions between enzyme and reactants, which induce catalytic barrier crossing (7,8,10,17,19).…”
Section: Spectator Probe Dipoles In the Ksimentioning
confidence: 99%
See 1 more Smart Citation
“…Two opposing and limiting theories of enzyme catalysis revolve around the nature of mechanical and electrostatic fluctuations in the enzyme active site. In one of the theories, fast (approximately picosecond) vibrations (protein breathing modes) and a network of coupled motions within the enzyme-substrate complex have been hypothesized to be linked to transition state formation and reduction of the barrier for chemical change (10,13,15,21). It has also been suggested that dynamic excursions of active site architecture on the picosecond timescale create variable electronic interactions between enzyme and reactants, which induce catalytic barrier crossing (7,8,10,17,19).…”
Section: Spectator Probe Dipoles In the Ksimentioning
confidence: 99%
“…The origins of the enormous catalytic power of enzymes are still not well understood despite enormous effort (1)(2)(3)(4)(5)(6). In particular, the functional role of fast picosecond protein motions in catalysis and the dynamic nature of the transition state barrier crossing is a subject of ongoing and current debate (7)(8)(9)(10)(11)(12)(13). Theoretical studies have suggested that fast vibrations in enzymes might generate transition state conformations conducive to the chemical reaction (7,8,(14)(15)(16)(17)(18)(19)(20)(21), a familiar concept for reactions in ordinary solvents (22).…”
mentioning
confidence: 99%
“…Some workers believe that motions of the protein promote tunnelling Antoniou and Schwartz, 2001;Mincer and Schwartz, 2003;Mincer and Schwartz, 2004;Johannissen et al, 2007;Johannissen et al, 2008;Pang et al, 2008), while others believe that the degree of tunnelling is similar in enzymes and their equivalent reference reactions, i.e. in solution, and hence the effect is not catalytic (Hwang et al, 1991;Hwang and Warshel, 1996;Olsson et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…[8] The enzyme reaction cycle is completed by long-range electron transfer to the type 1 copper protein azurin following assembly of an AADH-azurin electron transfer complex. [9][10][11] Insight into the reaction cycle has come from detailed analysis of the crystal structures of reaction intermediates, [8,9,12] computational simulations of the reaction chemistry [8,13,14] and isotope analysis of the proton transfer step using fast reaction stopped-flow methods. [5,15,16] These studies have provided a detailed appreciation of the reaction chemistry, whilst emphasizing the importance of proton transfer by quantum tunnelling mechanisms (for example, with tryptamine substrate).…”
Section: Introductionmentioning
confidence: 99%